The Nabawiyah-based Character Education and Pancasila Values in The Moral Development of SKIS Students - Nugraha, Saka Mahardika Oktav; Supriyanto, Supriyanto; Ambarsari, Arum; Septiono, Aris (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2025)
This study explores the integration of Nabawiyah character education values with the principles of Pancasila in shaping students’ moral character at Sekolah Karakter Imam Syafi’i (SKIS). Using a qualitative phenomenological approach, this research involved interviews, observations, and documentation with school principals, character teachers, students, and parents. The results reveal that SKIS implements the values of 'faith, learning, and creation' as the core of character development, which aligns with Pancasila’s values of belief in God, humanity, and social justice. The study concludes that Nabawiyah character education reinforces national identity and moral integrity, emphasizing that moral education rooted in prophetic traditions and Pancasila values can produce learners who are spiritually grounded, intellectually critical, and socially responsible.